2020
DOI: 10.21203/rs.3.rs-59490/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parent and Provider Perspectives on Factors Influencing Treatment-Seeking and Recovery After Hospital Discharge Among Undernourished Children Aged 2-23 Months in Bangladesh

Abstract: Background: Post-hospital discharge mortality is high among undernourished children in many low and middle-income countries; often exceeding in-patient mortality rates. Although a number of studies have highlighted a range of potential socio-cultural, economic and health system factors influencing paediatric post-discharge treatment-seeking and recovery, including in Bangladesh, few studies have explored parent and provider perspectives.Methods: As part of a large, multi-country prospective cohort study - the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Nineteen of the twenty-two children were reported by family members to have fully recovered by the time we completed our interviews and three children had died. In an earlier publication, we described treatment-seeking pathways for the undernourished children in the CHAIN cohort, and key in uences on treatmentseeking actions and recovery [48]. Across what were often lengthy treatment-seeking pathways, we showed that important in uences were hospital advice and media campaigns, social and nancial support from family members and others, and cost of treatment.…”
Section: Interviewee Characteristics and Overall Treatment-seeking Pamentioning
confidence: 78%
“…Nineteen of the twenty-two children were reported by family members to have fully recovered by the time we completed our interviews and three children had died. In an earlier publication, we described treatment-seeking pathways for the undernourished children in the CHAIN cohort, and key in uences on treatmentseeking actions and recovery [48]. Across what were often lengthy treatment-seeking pathways, we showed that important in uences were hospital advice and media campaigns, social and nancial support from family members and others, and cost of treatment.…”
Section: Interviewee Characteristics and Overall Treatment-seeking Pamentioning
confidence: 78%